Knowledge of wild edible mushrooms depending on educational level in the Region of Varna - Tsonka Dimitrova; Nikoleta Ivanova; Galina Yaneva (Journal of BioScience and Biotechnology, 2023)
Purpose Numerous wild edible mushrooms are relatively well-known in Bulgaria and many countries all over the world. The objective of this inquiry study was to analyze some peculiarities of local knowledge of such mushrooms depending on inhabitants’ educational level in the Region of Varna, Bulgaria. Materials and methods We performed a study of 200 adult individuals, 100 males and 100 females, on the territory of the Region of Varna using anonymous inquiry with a set of 12 concrete items dealing with respondents’ knowledge of wild edible mushroom and focusing on the role of their educational level for this knowledge. Statistical data processing was carried out using descriptive, variation and correlation analysis. Statistical significance was considered at the level of p<0.05. Results There was prevalence of the respondents with higher education. A total of 122 respondents (61% of the cases) could recognize wild edible mushrooms in the Region of Varna. The respondents with secondary education are most informed about these mushrooms. Numerous mushroom nominations of single concrete mushroom species were reported by the respondents. The edible boletus Boletus edulis Bull was the most commonly recognized wild edible mushroom. Respondents’ elementary educational level correlated statistically significantly with knowledge acquisition of wild mushrooms (Pearson’s coefficient=30.032; p<0.001). Conclusion This inquiry study demonstrated a satisfactory extent of awareness of these respondents with secondary, elementary and higher education concerning the wild edible mushrooms in the Region of Varna.